Comparative study of the changes in kinematic and kinetic characteristics of the badminton forehand clear service after the use of different types of feedback - Panagiotis, K.; Evaggelia, G.; Papadopoulos, C. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction Many coaches try to improve the performance of their athletes by given them cues and instructions about the way they act before, during, or after the execution of a motor skill. To give this information, they usually use Modeling, or Feedback. Both of these methods effect the performance in different ways. The purpose of the present study was to investigate the specific changes (1) in kinematic, and (2) kinetic characteristics of Forehand Clear Service if these exist, after the use of Learning of Observation and Verbal Feedback as methods of information. Methods 21 amateur badminton athletes participated in the study (Age 11.4 ± 0.3 years, body mass: 46±0.2 kg and height 155 ±2.75 cm). They were separated in three groups of 7 individuals based in the accuracy of service:Learning of Observation group (LOG), Verbal Feedback group (VFG) and control group (CG). The athletes followed an 8-week program with 45 minutes sessions twice per week. 20 points in the kinematic system were totally studied based on the principals of Kinematic analysis (Tsarouhas 1983, Hay and Reid 1988, Allard, Stokes and Blanchi 1995), as well as, the pre-existing researches in the area of Athletic Biomechanics, that dealt with kinematic analyses of multi-joint tasks (Wadell 2000). Variables related to displacement, velocity, angles, angular velocities, time, forces and vertical maximal force was evaluated. Results Repeated Measurements was applied to the pre training variables. Dynamic and kinematic variables are depicted on a table.